Carotenoid content in pumpkin from different locality in Malaysia - Othman, Rashidi; Hashim, Yumi Zuhanis Has-Yun; Jaswir, Irwandi; Shahidan, Norshazila (2012)
The increasing demand of carotenoid in global market has led to the analysis of carotenoid content in a variety of fruits and vegetables. In this study, pumpkins from different locality in Malaysia were analyzed. Pumpkin is believed to have health benefits due to its carotenoid content and other anti-oxidant compounds. UV-VIS spectrophotometer and HPLC analysis was conducted to analyze the total carotenoid and individual carotenoid in pumpkin. The total carotenoid content in pumpkin from different localities in Malaysia was ranged from 21.78 ug/g to 33.45 ug/g.